Purification to homogeneity of B cell stimulating factor. A molecule that stimulates proliferation of multiple lymphokine-dependent cell lines (The Rockefeller University Press, 1986)
Murine B cell stimulating factor 1 (BSF-1) was purified to homogeneity from supernatants of a stimulated thymoma cell line. A protein of 18.4 kD with a unique N-terminal amino acid sequence was identified. BSF-1 had a sp act of at least 3.28 X 10(8) U/mg. In addition to its B cell- stimulatory activity, BSF-1 also stimulated the proliferation of several IL-2- and IL-3-dependent cell lines. We conclude that BSF-1 is both a growth factor and a differentiation factor. Finally, these results also suggest additional biologic properties of BSF-1 on lineages besides B lymphocytes.